Evaluation of the functional rehabilitation outcomes of clients after receiving physical rehabilitation at TC Newman community day centre - Felix, Rochelle Karen (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)--Stellenbosch University, 2014.